2017
DOI: 10.1007/s11746-017-3020-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PNIPAM–PEG Double Hydrophilic Polymers Using Oleic Acid Macro Peroxide Initiator

Abstract: This work refers to the synthesis of a new double hydrophilic thermo‐responsive polymer using fatty acid macroperoxide initiator, N‐isopropyl acryl amide (NIPAM) and polyethylene glycol with two primary amine ends (PEGNH2). For this purpose, oleic acid was spread out onto a petri dish and exposed to air oxygen at room temperature for 2 months. The obtained fatty acid macro‐peroxide initiator was used in the free radical polymerization of NIPAM in the presence of PEGNH2. Poly oleic acid‐g‐PNIPAM‐g‐PEG graft cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…1 were found to be 0.67 wt.% for Prici and 1.45 wt.% for Pcast while the precursors, pure ricinoleic acid and castor oil, showed less than 0.1 wt.% of peroxide. The peroxide content of Prici is nearly the same as that of oleic acid macroperoxide initiator, which was recently reported (Hazer et al, ). One of the confirmations of the peroxide formation in the macroperoxide initiators was the elemental analysis indicating an increase in the O% of oxidized castor oil and ricinoleic acid.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…1 were found to be 0.67 wt.% for Prici and 1.45 wt.% for Pcast while the precursors, pure ricinoleic acid and castor oil, showed less than 0.1 wt.% of peroxide. The peroxide content of Prici is nearly the same as that of oleic acid macroperoxide initiator, which was recently reported (Hazer et al, ). One of the confirmations of the peroxide formation in the macroperoxide initiators was the elemental analysis indicating an increase in the O% of oxidized castor oil and ricinoleic acid.…”
Section: Resultsmentioning
confidence: 97%
“…Peroxide analysis of Prici and Pcast was carried out according to the procedure reported in cited reference (Hazer et al, ). For example, a mixture of Prici (or Pcast) (1.0 g), 2‐propanol (30 mL), acetic acid (5 mL), and saturated aqueous solution of KI (1 mL) was refluxed for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auto-oxidation of oleic acid was carried out according to previously established works 37,38 with slight modifications. A small amount (18 g) of oleic acid was poured onto a petri dishes (Φ = 14.5 cm, oil thickness: 1.0 mm) and subjected to under air oxygen at room temperature for about 4 months.…”
Section: Autoxidized Polymeric Oleic Acidmentioning
confidence: 99%
“…Effect on flocculation efficiency of P200G1 at different temperature et al suggested that the LCST of the polymer increased with increases in the amount of PEG[26].…”
mentioning
confidence: 99%